The North Italian innovative project for common psychiatric disorders: Evaluating the output of a treatment model of an outpatient clinic for anxiety and depression - Caselli, Ivano; De Leo, Alessandra; Isella, Celeste; Bellini, Alessandro; Ielmini, Marta; Callegari, Camilla (Frontiers in Public Health, 2023)
Already in 2018 depressive disorders are considered the first causes of disability worldwide. The outpatient clinic for anxiety and depression at the university hospital of Varese represents a service that fully responds to the growing number of requests. About 1350 medical records have been opened from 2010 to December 2021. The most frequent presenting diagnoses include anxiety disorders (36%), severe stress and maladaptation syndromes (35%), and depressive episodes (18%). The outpatient clinic has proved to be a model with great impact on users offering a range of diagnostic and therapeutic offers responding to the requests of the community.